Nanoscale film morphology and property characteristics of dielectric polymers bearing monomeric and dimeric adamantane units. (15th April 2019) - Ree, Brian J.; Kobayashi, Shingo; Heo, Kyuyoung; Lee, Taek Joon; Satoh, Toshifumi; Ishizone, Takashi; Ree, Moonhor
Abstract: In this study, we report for the first time the thin film morphology and property characteristics of a series of adamantane-containing polymers, which were investigated by using synchrotron grazing incidence X-ray scattering, X-ray reflectivity and spectroscopic ellipsometry. The chemically incorporated monomeric and dimeric adamantane units could disturb regular chain packing, ultimately producing amorphous polymers. They further tend to randomize chain orientations even in nanoscale thin films; surprisingly, random chain orientations could be achieved even for thermally-annealed thin films, which are quite different from the in-plane orientations of conventional polymer films being enhanced by thermal annealing. As a result, isotropic optical refractive indices and dielectric constants could be demonstrated even in nanoscale thin films, which are highly demanded for the production of advanced microelectronic devices. Moreover, the adamantane units incorporated into the backbone and as primary side groups could significantly reduce the dielectric constant, refractive index, critical angle, electron density and mass density of polymer. Overall, the positive impacts of incorporated adamantane units are huge on the polymer morphology and properties. All adamantane-containing polymers of this study are suitable materials for advanced microelectronics, which can replace current workhorse dielectrics, such as silicon oxide, silicon nitride, and polyimides, being used in microelectronic devices. Graphical abstract: Image 1 Highlights: Adamantane moieties incorporated in polymer disturb chain packing order severely. Adamantane units randomize chain orientation even in thermal-annealed thin films. Adamantane moieties produce zero or near zero birefringence of nanoscale films. Adamantane units lead zero or near zero anisotropy of dielectric constant of films.